Improving Students' Writing Skills by Using Pictures and Picture Method at Junior High School - Natalia Widya Pasca Tarigan; Esra Elisabeth Panjaitan; Peronika Simbolon; Johannes Fikki Damanik (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This study aims to investigate the improvement of students writing skill by using picture and picture method in SMP 21 Simalingkar B. The rational of this study to improve the writing lack on the descriptive text in SMP 21 Simalingkar B. This method of this study was Class Action Research and was carried out in cycle 1&2 in 25 students OF VIII B Medan. The writer collecting data using writing test, documentation, observation and interview. The data was analyzed by using qualitative and descriptive techniques. Based on the recapitulation in the cycle 1 and cycles 2 shown the improvement of students’ writing skill . The percentages in cycle 1 and cycles 2,were 44,8% for pretest, 48,8% for posttest in the cycle 1 and 71,84% for pretest , 81,44% for post test in cycle 2.By on the result of this study, the using of picture and picture method can improve students skills and classroom situation in writing text